Potential Habitat and Priority Conservation Areas for Endangered Species in South Korea - Soyeon Park; Hyomin Park; Sangdon Lee (Animals)
Anthropogenic threats from human activity have significantly altered global ecosystems, resulting in habitat destruction and fragmentation, biodiversity loss, and species extinction. The identification and establishment of protected areas for the conservation of threatened species is thus required to mitigate the impacts of these threats. This study identified priority conservation areas (PCAs) for endangered mammals, birds, amphibians, and reptiles in South Korea using ecological modeling. In particular, we used the MaxEnt model to determine the potential distributions of endangered species and Zonation software to prioritize conservation areas. In doing so, we aimed to identify key environmental factors that influence the distributions of the target species and to identify ecologically critical areas using gap analysis based on the first-grade areas on the ecology and nature map (ENM). The results indicated that the highest priority areas for endangered species varied by taxon, with endangered mammals found primarily in forested areas, endangered birds on inland plains, and endangered amphibians and reptiles within marine and stream regions. The gap analysis revealed a very low overlap between ecological areas and high-priority areas for endangered birds and amphibians. This suggests that the first-grade areas on the ENM mainly represent areas with high vegetational coverage. These findings highlight the need to reassess existing protected areas and designate PCAs for endangered species independently from the ENM. This study represents a foundational assessment that can be used to inform conservation planning and prompt continued ecological research in support of biodiversity conservation efforts.